PEMANFAATAN INSTITUTIONAL REPOSITORY SEBAGAI SUMBER PEMBELAJARAN BAGI SIVITAS AKADEMIKA UNIVERSITAS MUHAMMADIYAH MALANG - Laila Rifa’atul Azizah; Nur Ishmah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
Each college certainly has a lot of work that has been produced by all of its academicians. Various works are stored in a database in the form of digital content called repositories. University of Muhammadiyah Malang (UMM) Institutional Repository (IR) is a place to store various scientific works produced by UMM academicians. But there are still many who do not know the existence and function, this makes IR underutilized. The purpose of this paper is so that all academics can know and utilize the maximum possible IR facilities. The method used is qualitative. The focus in this study is to explain the use of institutional repositories as educational resources for the academic community of the University of Muhammadiyah Malang. Data collection techniques use observation and documentation. There was a drastic increase in IR access statistics in 2018. This shows that the socialization carried out by the library regarding the IR to its users has resulted. There are so many functions of IR that the academic community has not yet known that their use is not fully utilized. The functions of IR include searching for collections, uploading independent writings, and most importantly, as a source of learning for all academics.